Nilai -Nilai Pendidikan dalam Karya Tari Kedurai Imbang Semato Alam - Venny Rosalina (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine the educational values ​​in the work of the Kedurai Imbang Semato Dance. The research method used is a qualitative method, descriptive analysis. The distribution of the analysis sheet was carried out on the respondents of the Kedurai Imbang Semato Dance. Data collection techniques using observation, interviews, and documentation. Data analysis is done by reducing data, presenting, and drawing conclusions or verification. From the research that has been done, the following results were obtained. The work of the Kedurai Imbang Semato dance is an imbalance of good and bad behavior between humans and humans, humans and the creator and humans and nature. Therefore, these four words have a relationship that becomes a single unit in the work of this work, this dance work is not only an embodiment and traditional ceremony but also contains values ​​that contain social and religious teachings in everyday life. Today, the educational values ​​include natural educational values, cultural values, ethical values, aesthetic values, togetherness values, self-confidence values, hospitality values, mutual respect values, communication values, populist values, and creativity values.